Utilizing Social Return on Investment (SROI) as a framework for sustainable social investment: insights from flood mitigation - Dona Raihana Don Ramli,; Kadaruddin Aiyub,; Sarina Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, the increasing scarcity of resources and rising demands have created substantial challenges for social investment, impacting both profit-oriented and nonprofit organizations. Stakeholders across this spectrum, ranging from for-profit enterprises to nonprofit organizations, striving to adapt to rapid economic changes, face obstacles in securing funding, primarily due to difficulties in demonstrating the value of their investments. This challenge is exacerbated by the weaknesses often associated with Corporate Social Responsibility (CSR) initiatives, which can include a lack of measurable impact and insufficient alignment with stakeholder needs. Many CSR efforts often criticized for short-term focus and lack of measurable impact, contribute to skepticism among stakeholders regarding their effectiveness. Recognizing these challenges, there is a growing emphasis on sustainable investments that integrate social, economic and environmental returns. This article explores the concept of sustainability within the framework of the triple bottom line and the Sustainable Development Goals (SDGs), specifically focusing on the Sungai Muda Flood Mitigation Program (SMFMP), Kedah involving quantitative data. Using Social Return on Investment (SROI) analysis, the study finds a positive social return of RM 4,892,641,540.00, meaning the program delivers RM 4.88 in social benefits for every ringgit invested, across social, economic and environmental elements. These findings underscore the SMFMP's potential as a valuable social investment, offering substantial benefits for individuals, communities and society. The study suggests that the SROI is a useful tool for stakeholders, including government bodies and CSR initiatives to integrate social and environmental values into economic decision-making.